Modifying the Thioester Linkage Affects the Structure of the Acyl Carrier Protein. (2nd July 2019) - Sztain, Terra; Patel, Ashay; Lee, D. John; Davis, Tony D.; McCammon, J. Andrew; Burkart, Michael D.
Abstract: At the center of many complex biosynthetic pathways, the acyl carrier protein (ACP) shuttles substrates to appropriate enzymatic partners to produce fatty acids and polyketides. Carrier proteins covalently tether their cargo via a thioester linkage to a phosphopantetheine cofactor. Due to the labile nature of this linkage, chemoenzymatic methods have been developed that involve replacement of the thioester with a more stable amide or ester bond. We explored the importance of the thioester bond to the structure of the carrier protein by using solution NMR spectroscopy and molecular dynamics simulations. Remarkably, the replacement of sulfur with other heteroatoms results in significant structural changes, thus suggesting more rigorous selections of isosteric substitutes is needed. Abstract : Der Effekt des Austauschs des Thioester‐S‐Atoms eines Acyl‐Carrier‐Proteins (ACP) gegen N oder O zum Erhalt stabilerer Amid‐ oder Esterbindungen wurde mit NMR‐Spektroskopie und MD‐Simulationen studiert. Obwohl ACP mehr als 1000 andere Atome enthält, resultiert der Austausch dieses einen Atoms in signifikanten strukturellen Störungen. Die geeignete Wahl isosterer Surrogate zur Entwicklung chemo‐biologischer Hilfsmittel erfordert daher eine gründliche Evaluierung.